Hubungan Intensitas Polusi Isolator Jaringan Distribusi di Sumatera Utara dengan Jarak Lokasi Isolator dari Pantai - L. Tobing dan Mustafriend Lubis, Bonggas (Jurnal Teknik Elektro, 2007)
This paper reports the result of research about the pollution intensity of the insulator of 20 kV electrical distribution network in North Sumatera. It has investigated that the pollution intensity of the insulator of 20 kV electrical distribution network in North Sumatera is in low category. The pollution intensity of an insulator is decrease if the distance of mentioned insulator more far away from the seashore. If the distance of insulator from seashore about 40 km, the decreasing of pollution intensity reach to Â± 50 % of pollution intensity of insulator that close to the seashore. The pollution intensity of insulator almost constant if the distance of insulator from seashore is between 40 km to 80 km. It means that the salt contained on air which is blow from the sea is not influence on insulator pollution if the distance of mentioned insulator from seashore more than 40 km Abstract in Bahasa Indonesia : Paper ini melaporkan hasil penelitian tentang tingkat intensitas polusi pada isolator jaringan distribusi hantaran udara 20 kV di Sumatera Utara. Ditemukan bahwa tingkat intensitas polusi isolator jaringan distribusi hantaran udara 20 kV di Sumatera Utara termasuk kategori ringan. Intensitas polusi pada suatu isolator semakin rendah jika isolator semakin jauh dari pantai. Setelah jarak isolator dari pantai mencapai kurang lebih 40 km, intensitas polusi pada isolator turun Â± 50 % dari intensitas polusi isolator yang terdekat ke pantai. Pada jarak di antara 40 - 80 km dari pantai, intensitas polusi isolator hampir konstan. Artinya, kandungan garam yang dibawa angin laut tidak berpengaruh lagi terhadap polutan isolator jika jarak isolator dari pantai lebih dari 40 km. Kata kunci: distribusi, isolator, polusi, ESDD